Air Monitoring and Pollution Mitigation System in Urban Areas Using IoT - Aminuddin, Harris; Tarigan, Dito Arief Maulana; Dalil, M (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
Urban air monitoring and pollution mitigation systems are important efforts to maintain air quality in increasingly dense urban environments. This project aims to design and implement an Internet of Things (IoT)-based system that is capable of monitoring air quality and mitigating pollution automatically. This system used a Sharp GP2Y1010AU0F dust sensor to detect dust particles, a DHT22 sensor to measure temperature and humidity, and an HC-SR04 ultrasonic sensor to detect water levels in case of flooding. Additionally, it used the SG90 servo to automatically open and close the water valve, and 5V mini water pump to spray water from the underground tank, thereby reducing air pollution levels. The implementation of this system was carried out using plastic containers separated by plywood as a water storage medium and sensor installation. Data from sensors was sent to Blynk's IoT Platform for real-time monitoring. Apart from that, this system was also integrated with Telegram to provide notifications to residents if pollution levels worsen. Hence, they can immediately take preventative action by staying at home. Test results showed that the system was able to detect changes in air quality and water levels with precises accuracy. Apart from that, this system can also carry out pollution mitigation measures automatically by spraying water when pollution levels exceed a predetermined threshold. This project is expected to contribute to improving air quality in cities and can be widely implemented in various cities with high levels of pollution.